Design of novel lanthanide-doped core–shell nanocrystals with dual up-conversion and down-conversion luminescence for anti-counterfeiting printing. Issue 20 (2nd May 2019) - Xie, Shaowen; Gong, Guo; Song, Ya; Tan, Haihu; Zhang, Changfan; Li, Na; Zhang, Yanxian; Xu, Lijian; Xu, Jianxiong; Zheng, Jie
Abstract : Mono-dispersed, dumbbell-shaped lanthanide-doped NaYF4 @NaGdF4 core–shell nanoparticles with dual-mode fluorescence were synthesized for anti-counterfeiting. Abstract : Development of advanced luminescent nanomaterials and technologies is of great significance for anti-counterfeiting applications in global economy, security, and human health, but has proved to be a great challenge. In this work, we design, synthesize, and characterize mono-disperse, dumbbell-shaped lanthanide-doped NaYF4 @NaGdF4 core–shell nanoparticles (CSNPs) with dual-mode fluorescence by coating the NaGdF4 :Ln′ 3+ shell onto NaYF4 :Ln 3+ core nanospheres via a two-step oleic acid mediated thermal decomposition process. Different from the conventional synthesis method to produce spherical nanoparticles, the epitaxial growth of the NaGdF4 :Ln′ 3+ shell onto the nanosphere cores and the lattice mismatch between β-NaGdF4 and β-NaYF4 nanocrystals enable the formation of dumbbell-shaped CSNPs, as evidenced by the morphological evolution of CSNPs and as explained by the Ostwald ripening growth mechanism. By tailoring different doped lanthanide ions in the core and the shell, the resultant CSNPs exhibit tunable but different up-/down-conversion luminescence under the irradiation of a 980 nm laser and 254 nm UV light, respectively. Finally, these hydrophilic CSNPs are further fabricated into environmentally benign luminescent inks for inkjet printing to create a variety of dual-mode fluorescent patterns (peacock, temple, and a logo of "Hunan University of Technology") on different paper-based substrates (A4 paper, envelope, and postcard). Our dual-mode light-responsive CSNPs, along with an easy fabrication method, provide a simple and promising material and technique for anti-counterfeiting applications.